The Implementation of Restaurant Tax in Tomohon - Novia Sumarab; Wilson Bogar; Fitri Herawati Mamonto (Syntax Corporation Indonesia, 2022)
Tomohon is one of the tourist city destinations in North Sulawesi Province has a high potential to be developed. Restaurant Tax is a tax whose existence is essential as a source of Original Local Government Revenue (PAD). The restaurant tax revenue target consistently increases every year, and the realization of restaurant tax revenue has not fully met the set target. The difference between the realization of restaurant tax revenues and the target of restaurant tax revenues indicates that the potential has not been optimally explored. This study aimed to analyze the implementation and potential contribution of the Restaurant Tax in Tomohon. The data used in this study are primary data and secondary data. The analytical method used in this research is a descriptive qualitative method and implementation analysis. The analysis results show that the potential value of Restaurant Tax is substantial compared to the realization of Restaurant Tax receipts. This difference shows that the actual potential is also immense. However, the local government has not explored it optimally. The implementation of the Restaurant Tax shows that the collection and management of the Restaurant Tax in Tomohon have not gone well. The analysis results show that the restaurant tax potential affects Tomohon's PAD.